DISCIPLINE SCHOOL’S INFLUENCE TO DO NOT BRING CAM HANDPHONE TOWARDS FRESHMENT LEARNS OF STUDENT IN JUNIOR HIGH SCHOOL 7 AT KOTABUMI - Alex Lendro Juniarto Alex Lendro Juniarto; Dr.Adelina Hasyim, M.Pd. Dr. Adelina Hasyim, M.Pd.; Drs. Julyaden Abdul Hay Drs. Julyaden Abdul Hay (Jurnal Kultur Demokrasi, 2012)
DISCIPLINE SCHOOL’S INFLUENCE TO DO NOT BRING CAM HANDPHONE TOWARDS FRESHMENT LEARNS  OF STUDENT IN JUNIOR HIGH SCHOOL 7  AT KOTABUMI  Alex Lendro Juniarto, Adelina Hasyim, Zulyaden Abdulhay   ABSTRACT   The aimed of this research was to explain how the influence of upright discipline school  to  do  not  bring  cam  handphone  toward  freshmen  learns  of  student  class VII-VIII  in  Junior  High  School  7  at  Kotabumi  on  2011/2012.  Method  used descriptive  method  with  sample  as  many  as  35  respondents.  The  main  data collecting technique used inquiry.  Based  on  data  analyses  got  result  that  there  upright  discipline  school  to  do  not bring cam handphone toward freshmen learns of student class VII-VIII in Junior High  School  7  at  Kotabumi.  It  proved  by  Chi  Quadrate  formulation  x2 account was higher than x2 table (x2 account ≥ x2 table) as big  as 15,96 ≥ 9,94. Then did comparison  between  C  and  Cmax,  with  result  0,69  and  it  belonged  to  high categories based on Sugiyono.  Key Word: Influence, Discipline, Handphone, Freshmen Learn.